ALIENATION’S PERFECT EXAMPLE “THE NAMESAKE,” NOVEL BY JHUMPA LAHIRI - AHMAD, WAHAJUDDIN (IJRDO- Journal of Educational Research, 2023)
Jhumpa Lahiri's “The Namesake” tells the story of the Ganguli family including Ashima, Ashoke, Gogol and Sonia. Most of the novel revolves around Gogol and his life, as he tries to come to terms with his identity. During most of his childhood and adolescence, he had trouble accepting his name. In his novel “The Namesake,” Lahiri talks about the alienation, fear and disillusionment his characters face after moving abroad. In “The Namesake,” Ashima and Ashoke emigrate to the United States. Two characters emigrate to the United States due to socioeconomic factors.